A finite element thermal analysis of various dowel and core materials - Shanti Varghese; Padma Ariga; T V Padmanaban; R Subramanian (Wolters Kluwer Medknow Publications, 2012)
Aim: Thermal analysis of the temperature and stress distribution of parallel sided, threaded and non-threaded dowels and core materials under thermal loading within a maxillary central incisor using a three dimensional finite element study. Materials and Methods: 3D models of endodontically treated maxillary central incisor with parallel sided, threaded and non- threaded post and core materials were simulated using the ANSYS software. Materials simulated were parallel sided cast gold post and core, parallel sided fibre reinforced composite (FRC) post and core, and parallel sided, threaded, prefabricated stainless steel post and amalgam core. Thermal loads simulating hot (60 degree C/ 333K) and cold (15 degree C/288K) liquid were applied for 15 seconds at the incisal edge. The temperature changes at the selected nodes were obtained on the various post and core materials, interface between post and dentin, interface between core and dentin, within the dentin and within the cement layer. Results: Temperature and stress distribution pattern were represented in numerical and color coding and results interpreted. Thermal stresses arises as a result of temperature changes. A decreased temperature gradient of the metallic dowels and core (T1 hot - 0.002K, T3 hot - 1.071K, T1 cold -0.99K, T3 cold - 0K) were obtained than that of the FRC dowel and core of 1.982K(hot) and1.55K(cold) respectively due to the higher thermal conductivity of the metals. Higher thermal stress values of 3.567 Mpa(hot) and 3.092 Mpa(cold) respectively were obtained for the FRC dowels and higher stress values of 39.679 Mpa(hot) and 57.855 Mpa(cold) respectively were also obtained for the FRC cores. These values indicated that thermal stresses of the FRC dowel and core were greater than that of cast gold dowel and core and prefabricated stainless steel dowel and amalgam core due to its high coefficient of thermal expansion. Maximum stress values of the FRC dowel and core of 1.87 Mpa(hot) and 2.57 Mpa(cold) respectively were also generated in the cement layer, core and metal ceramic crown. The junction of the metal ceramic crown and dentin demonstrated the maximum stress. Higher thermal stress values of 59.162 ± 10 Mpa were obtained in the restoration and the coronal portion of the dentin than the stress levels of .0039 ± 10Mpa in the supporting bone due to an increased thermal expansion. Conclusion: Non-metallic dowel and core materials such as fibre reinforced composite dowels (FRC) generate greater stress than metallic dowel and core materials. This emphasized the preferable use of the metallic dowel and core materials in the oral environment.